Comparative genomics of Stutzerimonas balearica (Pseudomonas balearica): diversity, habitats, and biodegradation of aromatic compounds - Salvà-Serra, Francisco; Pérez-Pantoja, Danilo; Donoso, Raúl A.; Jaén-Luchoro, Daniel; Fernández-Juárez, Víctor; Engström-Jakobsson, Hedvig; Moore, Edward R. B.; Lalucat, Jorge; Bennasar-Figueras, Antoni (Frontiers in Microbiology, 2023)
Stutzerimonas balearica (Pseudomonas balearica) has been found principally in oil-polluted environments. The capability of S. balearica to thrive from the degradation of pollutant compounds makes it a species of interest for potential bioremediation applications. However, little has been reported about the diversity of S. balearica. In this study, genome sequences of S. balearica strains from different origins were analyzed, revealing that it is a diverse species with an open pan-genome that will continue revealing new genes and functionalities as the genomes of more strains are sequenced. The nucleotide signatures and intra- and inter-species variation of the 16S rRNA genes of S. balearica were reevaluated. A strategy of screening 16S rRNA gene sequences in public databases enabled the detection of 158 additional strains, of which only 23% were described as S. balearica. The species was detected from a wide range of environments, although mostly from aquatic and polluted environments, predominantly related to petroleum oil. Genomic and phenotypic analyses confirmed that S. balearica possesses varied inherent capabilities for aromatic compounds degradation. This study increases the knowledge of the biology and diversity of S. balearica and will serve as a basis for future work with the species.